1995
DOI: 10.1002/yea.320110203
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a glycerol/H+ symport in the halotolerant yeast Pichia sorbitophila

Abstract: Pichia sorbitophila is a halotolerant yeast capable of surviving to extracellular NaCl concentrations up to 4 M in mineral medium when glucose or glycerol are the only carbon and energy sources. Evidence is presented here that glycerol, the main compatible solute this yeast accumulates so as to maintain osmotic balance, is actively co-transported with protons. This transport system was shown to be constitutive, not needing induction by either glycerol or salt, and was not repressible by glucose. In glucose- or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 24 publications
(22 reference statements)
7
66
1
1
Order By: Relevance
“…Glucose-or glycerolgrown cells were harvested in the mid-exponential growth phase (variable optical density according to the strain) by centrifugation, washed twice and resuspended to a final concentration of " 30 mg ml − " (dry wt) in ice-cold distilled water. The methods used to determine (i) initial rates of proton uptake upon glycerol addition, (ii) initial uptake rates of ["%C]glycerol (Amersham) and (iii) the inhibitory effects of the protonophore CCCP (carbonyl cyanide m-chlorophenylhydrazone) and ethanol on uptake, have been described before (Lucas et al, 1990 ;Lages & Lucas, 1995 (Amersham) accumulation ratios were determined according to Lages & Lucas (1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose-or glycerolgrown cells were harvested in the mid-exponential growth phase (variable optical density according to the strain) by centrifugation, washed twice and resuspended to a final concentration of " 30 mg ml − " (dry wt) in ice-cold distilled water. The methods used to determine (i) initial rates of proton uptake upon glycerol addition, (ii) initial uptake rates of ["%C]glycerol (Amersham) and (iii) the inhibitory effects of the protonophore CCCP (carbonyl cyanide m-chlorophenylhydrazone) and ethanol on uptake, have been described before (Lucas et al, 1990 ;Lages & Lucas, 1995 (Amersham) accumulation ratios were determined according to Lages & Lucas (1995).…”
Section: Methodsmentioning
confidence: 99%
“…Besides the enhancement in production observed under stress, and taking into account that glycerol is a liposoluble molecule that leaks through the yeast plasma membrane, its retention should thus require an active response from the cell. In two different osmotolerant yeast species, Debaryomyces hansenii and Pichia sorbitophila, two different types of constitutive active-transport systems for glycerol have been described and characterized : a Na + \glycerol co-transport (Lucas et al, 1990) and a H + \glycerol symport (Lages & Lucas, 1995). Also in Zygosaccharomyces rouxii, an active-transport system for glycerol has been described .…”
Section: Abbreviationsmentioning
confidence: 99%
“…Initial rates of glycerol uptake, external alkalinization upon glycerol addition, as well as in/out accumulation ratios, were determined as previously described [5,9,12,13]. The intracellular volume values used to determine intracellular glycerol molarity have been determined by Lages and Lucas [5].…”
Section: Glycerol Transport Studiesmentioning
confidence: 99%
“…During the last few years several studies dealing with glycerol transport mediated by membrane proteins have been published and it has been shown that glycerol can be taken up by the various transport systems present in eukaryotic cells, including facilitated diffusion [7], proton symport [8] and sodium symport [9]. Protein-facilitated glycerol uptake has been described for higher eukaryotic cells such as rat hepatocytes [10] and for microorganisms such as Neurospora crassa [11] and Streptomyces clavuligerus [12].…”
mentioning
confidence: 99%